2007
DOI: 10.1002/er.1292
|View full text |Cite
|
Sign up to set email alerts
|

Price determination of ETS allowances through the switching level of coal and gas in the power sector

Abstract: SUMMARYThis paper discusses the opportunities that exist for reducing greenhouse gases (GHG) emissions by switching from coal to gas-fired units in electricity generation, 'forced' by the European Union Greenhouse Gas Emission Trading Scheme (EU ETS) price level of CO 2 . It attempts to find efficient GHG cost profiles leading to a reasonable GHG emission reduction.In a methodological demonstration case (an electricity generation system consisting of two coal and two gas-fired power plants), we demonstrate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Probably the best-known result in permit market theory is that each firm chooses a level of abatement such that its MAC is equal to the permit price in every period, which implicitly defines the optimal amount of abatement: hard coal towards gas, because the former is more than twice as emissions-intensive per unit of output than the latter. Fuel switching is generally considered to be abatement method of choice in the EU ETS [4,22,23,25], given that there was not enough time between market setup and the end of the first phase for firms to alter production technology significantly. Because load factors for power generation are around 50%, a production shift from coal to gas is more likely in this than in other sectors covered by the market.…”
Section: Base Modelmentioning
confidence: 99%
“…Probably the best-known result in permit market theory is that each firm chooses a level of abatement such that its MAC is equal to the permit price in every period, which implicitly defines the optimal amount of abatement: hard coal towards gas, because the former is more than twice as emissions-intensive per unit of output than the latter. Fuel switching is generally considered to be abatement method of choice in the EU ETS [4,22,23,25], given that there was not enough time between market setup and the end of the first phase for firms to alter production technology significantly. Because load factors for power generation are around 50%, a production shift from coal to gas is more likely in this than in other sectors covered by the market.…”
Section: Base Modelmentioning
confidence: 99%
“…Fossil fuel prices play an important role in determining CO 2 emissions in both the short run -due to the substitution effect of fuel switching from emissions intensive fuels to less intensive alternatives (Delarue, Voorspools, and D'haeseleer, 2008;Delarue and D'haeseleer, 2007) -and the long run, through the income effect and the process of directed technical change. Ideally, prices for various fossil fuels used for energy production would be included as explanatory variables in our analysis.…”
Section: Datamentioning
confidence: 99%
“…Bredin and Muckley [14] investigated additional fundamentals such as equity prices, temperature deviations, and CDS and CSS by using the Johansen cointegration test. Wang and Bai [15] found that CDS and CSS had a positive and negative effect on allowance prices in EU-ETS, respectively and other studies took account of the switching behavior between gas and coal [16,17]. Relying on the cointegration method, Creti et al [17] investigated the relationships between carbon price and its drivers (oil price, the switching price between gas and coal, equity price index) during Phases I-II of the EU-ETS and showed that the equilibrium relationships existed in both phases, especially in Phase II.…”
Section: Introductionmentioning
confidence: 99%